High-efficiency dry powder aerosol delivery to children: Review and application of new technologies. (March 2021) - Bass, Karl; Farkas, Dale; Hassan, Amr; Bonasera, Serena; Hindle, Michael; Longest, P. Worth
Abstract: While dry powder aerosol formulations offer a number of advantages, their use in children is often limited due to poor lung delivery efficiency and difficulties with consistent dry powder inhaler (DPI) usage. Both of these challenges can be attributed to the typical use of adult devices in pediatric subjects and a lack of pediatric-specific DPI development. In contrast, a number of technologies have recently been developed or progressed that can substantially improve the efficiency and reproducibility of DPI use in children including: (i) nose-to-lung administration with small particles, (ii) active positive-pressure devices, (iii) structures to reduce turbulence and jet momentum, and (iv) highly dispersible excipient enhanced growth particle formulations. In this study, these technologies and their recent development are first reviewed in depth. A case study is then considered in which these technologies are simultaneously applied in order to enable the nose-to-lung administration of dry powder aerosol to children with cystic fibrosis (CF). Using a combination of computational fluid dynamics (CFD) analysis and realistic in vitro experiments, device performance, aerosol size increases and lung delivery efficiency are considered for pediatric-CF subjects in the age ranges of 2–3, 5–6 and 9–10 years old. Results indicate that a new 3D rod array structure significantly improves performance of a nasal cannula reducing interface loss by a factor of 1.5-fold and produces a device emitted mass median aerodynamic diameter (MMAD) of 1.67 μm. For all ages considered, approximately 70% of the loaded dose reaches the lower lung beyond the lobar bronchi. Moreover, significant and rapid size increase of the aerosol is observed beyond the larynx and illustrates the potential for targeting lower airway deposition. In conclusion, concurrent CFD and realistic in vitro analysis indicates that a combination of multiple new technologies can be implemented to overcome obstacles that currently limit the use of DPIs in children as young as two years of age. Graphical abstract: Image 1 Highlights: Key aerosol and device technologies are presented that maximize delivery to pediatric airways: Using these technologies gave <11% total loss from the nasal cavity to the third bifurcation branch. The aerosol grows from an MMAD of 1.5–3.2 μm, after 2 s residence time. 90% of aerosol size increase occurs in first 0.6 s.